Low complexity hybrid precoding method in mmWave massive MIMO system - Jianwei XIANG; Xiulan YU; Xiaorong JING (Dianxin kexue)
A low-complexity hybrid precoding method was proposed to design the hybrid precoding for mmWave massive MIMO system.Firstly,an initial radio frequency(RF)precoding matrix was constructed based on the singular value decomposition.Then an updated RF matrix was constructed by placing the vector which was constructed by the biggest left singular vectors of the residual matrix onto the last column of the initial RF matrix.By multiple iterations,the resultant RF precoding matrix can be obtained and the digital precoding matrix was designed based on the least square criterion.Theoretical analysis and simulation results show that the proposed algorithm greatly outperforms the hybrid precoding method based on orthogonal matching pursuit(OMP)algorithm with much reduced computational complexity.Additionally,the proposed hybrid precoding method has almost the same performance as the full digital precoding method when the number of data stream is relatively less.